Development of a finite element lumbar spine model to predict intervertebral disc herniation risk factors. Issue 1 (27th January 2022) - Rossman, Stephanie; Meyer, Eric; Rundell, Steven
Abstract: The objective of the current study was to develop a lumbar motion segment FE model that predicts disc herniation risk. The posterolateral nucleus extrusion force and disc pressure increased as the amount of flexion and magnitude of compression was increased in all loading scenarios. The nucleus extrusion force and posterior stress in the annulus both increased when exposed to a combination of compression and flexion. Results of the current study confirmed the authors hypothesis that the model would accurately predict herniation risk when exposed to a biomechanical environment known to cause herniations.